PENGARUH MODEL PROBLEM BASED LEARNING (PBL) TERHADAP KEMAMPUAN BERPIKIR KREATIF SISWA PADA MATERI KEANEKARAGAM MAKHLUK HIDUP DAN KLASIFIKASINYA - Haryati; Unita Sukma Zuliani Nasution; Dini Puji Anggraini; Taufiqurrahman; Ella Astika (Jurnal Sintaksis, 2024)
This study aims to determine the influence of the Problem Based Learning learning model on students' creative thinking skills on the diversity of living things and their classification. The type of research is a quasi-experiment with a Pretest Posttest Control Group Design research design. Sampling in this study was carried out using random sampling techniques. How to draw samples using a lottery system. The collected data was analyzed descriptively and using Manova analysis which was preceded by a hypothesis test, including Data normality test carried out using Kolmogorov-Smirnov statistics. The variant homogeneity test was carried out using Levene statistics. The colliniality test between the bound variables uses product moment correlation. All tests are carried out at a significance level of 5%. The results of the analysis of the statistical number F are equal to 31,523 and the sig. 0.000< 0.05. So the null hypothesis (Ho) is rejected and HA is accepted. This means that there is an influence of the Problem Based Learning learning model on students' creative thinking skills in the material "Diversity of living things and their classification". The results of the test of critical thinking skills and experimental creative thinking skills were higher than that of the control class. This is based on the results of Manova's analysis which obtained a statistical number of F equal to 19.292 and a significance number of 0.000 less than 0.05 for Pillai's Trace, Wilk's Lambda, Hotelling's Trace, and Roy's Largest Root. So the null hypothesis (Ho) is rejected and HA is accepted. This means that there is an influence of students' creative thinking skills between groups of students who study with the Problem Based Learning learning model.